Continental breakup–driven uplift instigated East Antarctic Ice Sheet formation - Thomas M. Gernon; Thea K. Hincks; Philip Goodwin; Guy J. G. Paxman; Sascha Brune; Eelco J. Rohling; Derek Keir; Jean Braun (Science, 2026)
Why Antarctica became glaciated ∼34 million years ago (Ma) remains debated, as relatively warm climates and sea temperatures appear inconsistent with ice sheet formation. Although a critical decline in CO 2 is considered primarily responsible, evidence suggests that other factors were important, too. We investigated whether regional topographic uplift, rooted in Jurassic continental breakup and mantle-surface feedbacks, enabled nucleation of the East Antarctic Ice Sheet (EAIS). By integrating geodynamic-topographic models with ice sheet and energy balance models, we show that progressive plateau growth in East Antarctica, including Eocene uplift of the Gamburtsev Mountains, pushed landscapes above the threshold for ice sheet nucleation by ∼45 Ma. Uplift enabled EAIS growth under warmer-than-expected climates, producing hemispheric asymmetry in early glaciation and reconciling Oligocene polar warmth with the onset of the modern icehouse world.